Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)
Keywords: chlorophyll; Chlorophyll: physiology; Juniperus; Juniperus: physiology; photoprotection; Pinus; Pinus: physiology; Plant Leaves; Plant Leaves: physiology; Quercus; Quercus: physiology; Seasons; Sunlight; Trees; Trees: physiology; xanthophyll cycle

Variations in Quercus ilex chloroplast pigment content during summer stress: involvement in photoprotection according to principal component analysis - Llorens, L.; Aranda, X.; Abadia, A.; Fleck, I. (FUNCTIONAL PLANT BIOLOGY, 2002)
We examined chloroplast pigment variation in holm oak (Quercus ilex L.) leaves for two periods under two climatic conditions, at midday during summer. We compared variation between control (unburned) plants and plants burned the preceding summer, since post-fire resprouts show higher photosynthetic rates and lower thermal energy dissipation. Principal component (PC) analysis was performed on nine pigment-content variables for the two periods separately. Two PC factors (PC1 and PC2) explained 83 and 84% of the variance of the data for each period. In both periods, PC 1 was marked by positive loading of pigments associated with light absorption or structural function namely neoxanthin, lutein, beta-carotene, chlorophyll a, and chlorophyll b. These pigments were only affected by leaf age. In contrast, PC2 was marked by high loadings of xanthophyll-cycle pigments (associated with photoprotection), and lutein-5,6-epoxide. Leaf content of these pigments was affected by climatic conditions. In the situations considered in PC analysis (leaf types, periods), the lutein-5,6-epoxide content presented a variation pattern similar to that of violaxanthin, and was significantly correlated with thermal dissipation of excess energy (represented by non-photochemical quenching or NPQ). These results suggest a relationship of lutein and lutein-5,6-epoxide with photoprotection.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: 6-epoxide; chlorophyll; lutein-5; photoprotection; Principal component analysis

A NONDESTRUCTIVE METHOD TO DETERMINE CHLOROPHYLL CONTENT OF LEAVES - Gratani, L (PHOTOSYNTHETICA, 1992)
A reliable non-destructive method for determining leaf chlorophyll (Chl) content on site uses a simple instrument, the Minolta SPAD-502. Calibration curves plotting Chl-meter readings against Chl content extracted were obtained for various sclerophyllous species of a Quercus ilex L. evergreen forest.
APS
Keywords: calibration curves; Chl content; chlorophyll; Quercus ilex L.

Influence of Temperature on the Effects of Water Stress on Quercus Species - SPYROPOULOS, C G; LAMBIRIS, M P (Annals of Botany, 1979)
Quercus coccifera L. and Q. ilex L. leaves, collected in winter, when the plants were in full turgor, were treated with polyethylene glycol (PEG) with a water potential of −48 and −65 bar, at 15 °C and at 30 °C, for 2 days. The response of each species differs with temperature as far as the plastid pigment, anthocyanin and soluble sugar content is concerned. Thus Q. ilex is affected more at 15 °C rather than at 30 °C, while in Q. coccifera, apart from a small increase in anthocyanins, no significant change was observed at 15 °C. On the contrary, at 30 °C significant changes were observed in all studied parameters. Chloroplast pigments decreased generally on the first day and their content either dropped further or increased to reach the control values on the second day. All treatments resulted in an increase in anthocyanin content. Soluble sugar content raised in Q. ilex at 15 °C and decreased in both species at 30 °C.
Keywords: anthocyanin; carotenoids; chlorophyll; oak; Quercus coccifera; Quercus ilex; Temperature; water stress